Hubungan Antara Keterampilan Metakognitif dengan Keterampilan Proses Sains Siswa Kelas IV SDN 15 Singkawang - Sari, Nur Fila; Marhayani, Dina Anika; Utama, Erdi Guna (LP. Ma'arif Janggan Magetan, 2023)
This study aims: 1) To describe the Metacognitive Skills of fourth grade students at SD 15 Singkawang. 2) To describe the Science Process Skills of grade IV students at SD 15 Singkawang. 3) To describe the relationship between Metacognitive Skills and Science Process Skills for fourth grade students at SD 15 Singkawang. This type of research is correlation research with a quantitative approach. The research population is class IV students at SDN 15 Singkawang. The sampling technique in this study was a purposive sampling technique. The sample in this research was class IV students at SDN 15 Singkawang, where the sample size was 26 students. The data collection technique in this study was based on test and non-test techniques, namely using the Science Process Skills questions with the material properties of light and the Metacognitive Skills questionnaire. The data analysis techniques used are the Prerequisite Test and Linearity Test. The research results show that, 1) The level of metacognitive skills is relatively high based on the overall average calculation of 71.22. 2) The level of students' science process skills is quite good with an average of 64.07. 3) There is a significant relationship between metacognitive skills and Science Process Skills for grade IV SDN 15 Singkawang with a determinant coefficient of 29.16%, t count of 3.14, and a correlation coefficient value (rs) of 0.54. Thus it can be concluded that for the level of Science Process Skills it is quite good while for Metacognitive Skills it is classified as moderate.